Logistic-like and Gauss coupled maps: The born of period-adding cascades - da Costa, Diogo Ricardo; Rocha, Julia G.S. [UNESP]; de Paiva, Luam S. [UNESP]; Medrano-T, Rene O. (Elsevier, 2021)
In this paper we study a logistic-like and Gauss coupled maps to investigate the period-adding phenomenon, where infinite sets of periodicity (p) form a sequence in planar parameter spaces, such that, the periodicity of adjacent elements differ by a same constant (ρ) in the whole sequence (pi+1−pi=ρ). We describe the complete mechanism that form this sequence from a closed domain of isoperiodicity. Changing a control parameter, infinite different periodicities ring-shaped take place in this domain promoting regions of chaoticity. In this environment several complex sets of periodicity arise aligning themselves in sequences of period-adding, which is a common scenario that appears in a great variety of nonlinear dynamical systems. The complete process is unraveled by applying the theory of extreme orbits.
Keywords: Chaos; Dissipative systems; Mappings; Nonlinear dynamics